Chemical and pharmacological studies on pereskia bleo Kunth. (Cactaceae) and choisya ternata Kunth. (Rutaceae) - Abdul Wahab, Ikarastika Rahayu (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2013)
Phytochemical and pharmacological investigations of Pereskia bleo (Kunth) DC (Cactaceae) and Choisya ternata Kunth. (Rutaceae) fractions were carried out. The chemical evaluation of P. bleo fractions resulted in the isolation and identification of two unreported compounds for the species, (β-sitosterol glucoside (8) and vitexin (9) which were isolated from the dichloromethane and ethyl acetate fractions, respectively, β-sitosterol (1) was isolated from the hexane fraction. This is the first report of the occurrence of vitexin, a C-glucosylflavonoid in Pereskia. This finding is relevant in chemotaxonomy as it confirms the trend of Cactaceae being able to synthesize C- glycosylflavonoids, posing Cactaceae and Didieraceae with similar status both morphologically and chemotaxonomically. Based on its popular uses among Malaysians, the fractions were evaluated for antioxidant, antinociceptive and anti-inflammatory activities. The results showed moderate pharmacological activity in all assays and can Justify its use in Malaysian folk medicine as a drug to treat rheumatism, among other inflammatory conditions. The moderate analgesic activity of the ethyl acetate fraction is not due to the presence of vitexin.
Keywords: Pharmacognosy, Ph.D.; Ph.D. Trinity College Dublin